The Role of Hospital Image in Building Patient Loyalty : A Systematic Literature Review - Subiantoro, Subiantoro; Praswati, Aflit Nuryulia; Romadhon, Yusuf Alam (Syntax Corporation, 2025)
This study aims to systematically review the role of hospital image in building patient loyalty through a Systematic Literature Review (SLR) and bibliometric analysis approach. Articles were searched using a combination of Boolean keywords for the period 2020–2025. The screening process followed the PRISMA protocol, resulting in 30 articles that met the final criteria for thematic and bibliometric analysis using VOSviewer. The results showed four main clusters: (1) the relationship between hospital image, service quality, and satisfaction; (2) the reputation of doctors and institutions as determinants of trust; (3) brand image and patient experience as predictors of revisit intention; and (4) trust and service quality as the main mediating mechanisms. Publication trends increased rapidly after 2023, with the focus shifting from classic satisfaction-based models to a new paradigm emphasizing patient experience and trust. This study provides conceptual and practical contributions for hospitals in managing their image, strengthening their digital reputation, and building patient loyalty in a sustainable manner through services oriented towards patient experience and emotional value.